Forms of specific expertise use during investigation of criminal offenses related to smuggling - Spitsyna, Hanna; Kovalev, Yurii (Archives of Criminology and Forensic Sciences, 2025)
In a joint article with Yuriy Kovalev, we consider the forms of using specific expertise during investigation of criminal offenses related to smuggling. Depending on the method of committing offense, object nature of smuggling, as well as other factors (time, place, instrument, characteristics of the subject), forms of specific expertise differ both in content and functional load. The lack of comprehensive developments within this issue makes the task of determining typical forms of specific expertise relevant. The purpose of this article is to identify and generalize typical forms of using special knowledge that are implemented during investigation of criminal offenses related to smuggling. It was found that the forms of using specific expertise during investigation of smuggling criminal offenses depend on the content of the criminal activity, the properties of the object of smuggling, methods of its movement, technical means involved and other circumstances. They include procedural, non-procedural and mixed forms that can have both evidentiary and indicative value. It is emphasized that rational application of specific expertise in an appropriate form significantly affects the quality of the pre-trial investigation, completeness of establishing circumstances of criminal offense commission and formation of an adequate evidence base.